Experimental study of factors affecting dust accumulation and their effects on the transmission coefficient of glass for solar applications. (November 2017) - Gholami, Aslan; Saboonchi, Ahmad; Alemrajabi, Ali Akbar
Abstract: Solar collectors and Photovoltaic panels are the most common applications of solar energy. Although how to increase the efficiency of these systems in different ways has been vastly studied and analyzed, the effect of dust accumulation on panel's and collector's efficiency has been largely ignored. To overcome this deficit, an experiment was developed in Isfahan, Iran, to investigate the factors affecting dust accumulation and their effects on the transmission coefficient of glass. The results indicate factors such as installation tilt, azimuth angle, dominant wind direction and the time in which samples are placed within the environment, are related to dust accumulation density on surface and transmission coefficient reduction. Up to 25% decline in the transmission coefficient caused by the accumulation of dust on the surface was observed during the 70-day test period. Given that the dust fall density is strictly depended on weather conditions during the test period, unlike previous studies, in this article the transmission reduction relation, instead of time is derived in terms of dust accumulation density on the surface. This equation is generalized and applicable to other regions and even different weather conditions. Highlights: The factors affecting dust accumulation on glass cover were investigated. The effect of settlement of dust on the transmission coefficient of glass was investigated. A generalized correlation form was introduced to predict dust accumulation effect in other regions and weather conditions.